Curriculum mapping as deliberation - examining the alignment of subject learning outcomes and course curricula - Lam, Bick Har; Tsui, Kwok Tung (Studies in higher education (Dorchester-on-Thames), 2016)
This article aims to evaluate the alignment between subject learning outcomes (SLOs) that represent the role of the Department of Curriculum and Instruction (C&I) and the course curricula documents. Content analysis was conducted to map SLOs in the curricula documents of a set of compulsory courses offered by the department of C&I. A hermeneutic perspective was adopted by four academic staff members who were involved in the mapping process, which considers curriculum scrutiny as an opportunity of reflective dialog. Findings suggest that though SLOs were adequately addressed in courses offered in various programs, the coverage and depth of studying SLOs may differ in different programs, such as Bachelor of Education and Post Graduate Diploma in Education. In this study, curriculum mapping was facilitated by deliberative dialog among participants, which made the mapping exercise a validating professional development activity. Implications are discussed. Recommendations regarding curriculum evaluation and teacher training are similarly suggested.